MODEL PEMBELAJARAN BERBASIS KEARIFAN LOKAL SULAWESI SELATAN UNTUK MENINGKATKAN PENGEMBANGAN KETERAMPILAN BERBICARA ANAK MELALUI KELONG, SASTRA TUTUR, DAN MANTRA - Muhammad Akhir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Speaking skills are the primary foundation for children's language development and a crucial instrument for interdisciplinary learning. In Indonesia, children's speaking skills, particularly at the elementary school level, still face serious challenges due to the dominance of text-based learning, the lack of space for oral expression, and the low utilization of local cultural contexts in learning. South Sulawesi has a legacy of local wisdom in the form of kelong (Bugis-Makassar folk songs), oral literature (folk tales, fairy tales, and advice), and mantras (spiritual rhythmic utterances) that serve as a medium for transmitting values, a means of traditional education, and a vehicle for communication training. These oral traditions have great potential to support children's speaking skills through rhythm, intonation, vocabulary, and authentic communicative expression. This study aims to develop a learning model based on local wisdom in South Sulawesi to improve children's speaking skills. The research method uses a Research and Development (R&D) approach with a modification of the Borg & Gall model. The study subjects involved 60 fourth-fifth grade students in two regencies, Bone and Gowa, with teachers acting as facilitators. Data were collected through speaking skills tests, classroom observations, interviews, and questionnaires, then analyzed using quantitative and qualitative approaches. The results showed significant improvements in aspects of speaking fluency, vocabulary mastery, public speaking courage, and children's expressive abilities. This study concludes that the integration of kelong, oral literature, and mantras into learning serves not only as a pedagogical strategy but also as an effort to preserve regional culture. The research's contribution lies in developing a culture-based learning model that can be replicated in similar contexts, as well as in strengthening children's oral literacy amidst the challenges of globalization and cultural homogenization.